Utilizando o protocolo Bittorrent DHT para viabilizar conectividade fim-a-fim de propósito geral em redes com servidores NAT - Silva, Josaias de Moura (Universidade Federal Rural do Semi-Árido, 2018)
As a result of using the, Network Address Translation (NAT) technique as a solution to the problem of IPv4 address limit, computers that connect to the Internet using this technique have lost the ability to communicate directly. In this scenario this work proposes a Node.js JavaScript library development that provides peer-to-peer (P2P) connectivity between peers with Internet connection through non-symmetrical NAT’s. The approach adopted to solve the connectivity problem was the use of the UDP Hole Punching technique using the BitTorrent DHT (Distributed Hash Table) as a rendezvous server role. Network simulations were used to verify the operation of the library and it was observed that it succeeded in providing the desired connectivity.
Keywords: BitTorrent DHT; UDP holepunching; Ponto-a-ponto; NodeJS; Peer-to-peer; Network address translation; CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO